Application of Theoretical Principles (Trize) in Solving Problems... Banks.. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The study seeks to apply the principles of the theory of Triz in resolving banking problems, as this theory is considered one of the most important tools to address and solve issues regarding improving organizational performance and management within institutions and to meet internal and external challenges that may arise.This research aims to offer solutions to banking problems in accordance with the principles of the theory of Triz as well as presenting theoretical and practical concepts of Triz theory and its objectives and principles.       The researchers relied on personal interviews with the managers and officials of departments to diagnose banking problems as a tool for collecting data, and then examined these problems and suggested solutions in accordance with Triz theory.